The Association of Statin Therapy with Liver and Pancreatic Fat Fraction in Type 2 Diabetes Mellitus - Mehmet Akif Parlar; Hakan Mutlu; Betül Doğantekin; İsmail Serhat Musaoğlu; Nisa Demirboşnak Albayrakoğlu; Mustafa Lütfi Yavuz; Zehra Buşra Özbolat; Mustafa Kaplan (Diagnostics)
Background/Objectives: It has been shown that the use of statins in patients with type 2 diabetes mellitus (T2DM) worsens hyperglycemia and hemoglobin A1c levels but may help in the preservation of pancreatic β-cell function. The potential role of a high pancreatic fat fraction (PFF) in this process has not yet been clarified. This study aimed to investigate whether the liver fat fraction (LFF) and PFF in T2DM patients is affected by statin therapy. Methods: This cross-sectional study involved a total of 140 T2DM patients, including both those who were receiving (n = 70) and those who were not receiving (n = 70) statin therapy. The mapping of the LFF and PFF utilizing the IDEAL-IQ sequence was conducted in magnetic resonance imaging. Results: In T2DM patients who used statins, the median PFF was higher compared to those who did not use statins (8.4 vs. 6.2%, p = 0.021), while the median LFF was found to be similar (8.4 vs. 8.9, p = 0.572). Variations in PFF were associated with the use of various statins (non-statin group: 6.2 vs. atovastatin: 8.7 vs. rosuvastatin: 3.2 vs. pitavastatin: 9.2, p = 0.004). The multivariable regression analysis indicated that insulin usage decreased log(LFF) by a factor of 0.16-fold (ꞵ ± SE = −0.16 ± 0.05, p = 0.010), and rosuvastatin usage reduced log(PFF) by 0.16-fold (ꞵ ± SE = −0.16 ± 0.07, p = 0.025), irrespective of other risk factors. Furthermore, the use of atorvastatin (ꞵ ± SE = 0.17 ± 0.06, p = 0.011) and pitavastatin (ꞵ ± SE = 0.19 ± 0.07, p = 0.008) were independently associated with an increase in log(PFF). Conclusions: In patients with T2DM, statin use did not show a significant effect on the liver fat fraction, but it caused differences in the pancreatic fat fraction. The observation of a lower pancreatic fat fraction in patients taking a rosuvastatin and atorvastatin dose of 40 mg/day suggests that different types and doses of statins may have varying effects on pancreatic fat accumulation.